The Effect of ADDIE-Based ESP Materials on Vocational Students’ Skills in Brackish and Marine Aquaculture Agribusiness - Warda Lessy; Karolis Anaktototy; Sophia Binnendyk (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study investigates the effect of ADDIE-based English for Specific Purposes (ESP) reading materials on vocational students’ reading comprehension in the Brackish and Marine Aquaculture Agribusiness program. The research addresses the issue of students’ low reading comprehension due to the use of general English materials that are not aligned with their vocational needs. A pre-experimental one-group pre-test and post-test design was employed, involving 25 vocational students selected through purposive sampling. The instructional materials were systematically developed using the ADDIE model to ensure relevance to students’ field of study. Data were collected through reading comprehension tests and a student effectiveness questionnaire. The results revealed a significant improvement in students’ reading comprehension, as indicated by an increase in the mean score from 62 (pre-test) to 81 (post-test), with a gain score of 19. The normalised gain score of 0.5 suggests moderate effectiveness of the intervention. Additionally, the questionnaire results showed a mean score of 4.3, indicating that students perceived the materials as very effective. The findings demonstrate that ESP-based reading materials, when developed systematically using the ADDIE model, can significantly enhance vocational students’ reading comprehension, motivation, and confidence. Therefore, integrating contextualised and discipline-specific materials into vocational English instruction is highly recommended to support both language proficiency and professional literacy.